An Electronic Device Reviewed by Diagnosing on the Modules Embodiment - Goeritno, Arief; Setyawibawa, Ika (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
An electronic device with various purposes needs in-depth study from the very beginning of the idea, before getting the final product. It relates to an essential role in providing user's infrastructure and service. The research objectives are to obtain the electronic circuits, modules, and devices by integrating the wiring. The research methods are conducted in the form of designing, manufacturing, assembling, and diagnosing. Designing stage is to obtain several electronic circuits as a liaison and the manufacturing stage to obtain the printed circuit board. The assembling stage is to obtain the gateway boards which controlled by the Arduino modules and diagnosing stage to obtain the interface device for communicating (IDC) is formed by integrating the wiring. Integrating several electronic circuits, modules, and devices have resulted in an IDC. Operating the IDC uses two different systems, i.e. from the telephony system to the radio-frequency system or vice versa with a half-duplex mechanism.